Cambios de radón en suelo y elementos químicos mayores y trazas en agua subterránea asociados a actividad sísmica - Peña García, Pablo (Universidad Autónoma Metropolitana, 2003)
In the last decades, many geochemical and geophysical studies have been performed in different countries having high seismic activity. Among these studies, those about gases behavior in the soil and groundwater have had special importance, 222Rn being one of the most important parameters. The objective of this work was the determination of radon behavior in soil and groundwater. Also, major and trace chemical elements were analyzed in groundwater from wells and springs located at Guerrero State and the Gulf of Mexico coasts, in Mexico. The Mexican Pacific coast is one of the most seismologically active areas in the world, due to the subduction of the Cocos and Rivera Plates under the North America Plate. On the other side at the Gulf of Mexico coast, low seismic activity occurs, however the Laguna Verde nuclear power plant (PNLV) is settled in the area and the seismicity studies should be known for nuclear safety. Radon measurements in soil and groundwater were carried out in long term measurements using solid state nuclear track detectors (LR-115). Eventually, automatic detectors were also used for continuous determinations in the short term (Clipperton probe). In some cases gamma radiation was analyzed in the soil by using thermoluminiscent detectors (CaSO4:Dy+PTFE). The physiochemical parameters analysis in water samples were determined by conventional wet chemistry. The water family typeswere determined with the Piper diagram. Trace elements were obtained using an inductively coupled plasma mass spectrometer (ICP-MS). The statistical analysis was carried out through principal compound analysis. The mineralogical composition of rock samples was also determined using conventional techniques and scanner electron microscope. In order to identify the crystalline compound in some rock samples an X-ray diffractrometer was used. The sampling sites were localized by means of a global positioning system (GPS). The sampling was performed along the Guerrero coast, from Guacamayas to Marquelia, from 1993 to 1998. At the Gulf of Mexico coast, sampling was performed at the PNLV and surrounding sites, from 1994 to 1996. Radon fluctuations, gamma radiation, major and trace chemical elements, were analyzed as a function of meteorological parameters, geologic characteristics and the local seismicity. At the PNLV results show relatively lowaverageradon concentration. Variations of radon valuesin the soil and groundwater were different at each sampling station and they were a function of the meteorological parameters and of the geologic characteristics. Rancho Nuevo station, located in a fracture zone, 35 km north of PNLV, showed the highest radon concentration. The lowest values were obtained at the PNLV station. The radon fluctuations were larger in the soil than in groundwater. Anomalies of radon values appeared during the rainy season; this behavior may be due to soil humidity because ofits coincidence with the rainy season. During the rainy season the major and trace elements analysis in groundwater samples showed a larger mineralization. A strong correlation Na-Cl was obtained during the dry season while, in both seasons a moderate correlation between (Ca-D) was obtained. Concerning the trace elements, strong correlations (Mn-Co-U) and (Rb-As) were also obtained during the winter season and additionally, at the dry season (Cu-Pb-B) and (Li-Rb) were strongly correlated. The seismic activity during the sampling period was sporadic and of low intensity and it could be observed that the fracture zone was the one that had higher radon values due to a preferential gaz flow. The fluctuations of soil radon at the Pacific coast showed an occasional dependence on the meteorological parameters. The maximum radon values were obtained mainly during the rainy season, as observed at the Gulf of Mexico zone. The local geology was the main factor that influenced the radon behavior; indicating that the gas behavior in soil depends on the substrate. The sampling sites located on residual soil showed lower values that those located on granitic and metamorphic soil. Also, sites close to each other and corresponding to the same geological zone presented similar behavior. An intense seismical activity was observed during the sampling campaigns. Most of the earthquakes were reported to be M> 4 and at shallow depth (<20 km). Soil radon behavior measured in the long term did not responded with peaks one to one to the local earthquakes, but showed global variations when located at a high seismical activity zone, with radon packages before and after the occurrence of some earthquakes. The springs chemistry correspondedto different water families, with different mineralization. They belong in general to waters from meteoric origin of recent infiltration. Different chemical element concentrations were found for each well or spring, due to the diversity of the rocks through which water circulates, as well as to the recharge patterns of the aquifers. Increases in chemical elements concentration were observed during the dry season. Radon concentration and gamma radiation fluctuations showed a moderate correlation in some cases, which can be explained due to the fact that termoluminiscent detectors were placed inside the radon exposure chamber. Differences in composition of rock types indicated differences in radon emanation and in gamma radiation levels in the studied zone. The groundwater analysis at Guerrero coast showed the presence of organic matter pollution due to the presence of near by human communities. The studied wells presented variations in the water composition. In the major and trace elements a group correlation was observed generating the separation of groups when variance analysis was performed, indicating that aquifers originate from different types of rock formations. The geochemical response of each aquifer depends on the specific geological context and on the recharge patterns. For seismic activity, at the Gulf of Mexico region, with sporadic and low magnitude earthquakes,differences in radon concentration were found only at the fracture zone. At the Pacific zone, anomalies related to the shallow seismicity were found for earthquakes magnitudes between (M 5 and 7), whose epicenters were located up to 60 km from the sampling station.; En las últimas décadas se ha realizado un gran número de estudios geofísicos y geoquímicos en diferentes países que presentan gran actividad sísmica. Entre los estudios que se han realizado, destacan aquellos relacionados con el comportamiento de gases en el suelo y agua subterránea, siendo el radón (222Rn) un parámetro importante. El presente trabajo tiene como objetivo la determinación de la concentración del radón en el suelo y en el agua subterránea, así como el análisis de elementos químicos mayores y trazas en agua subterránea de las costas de Guerrero y del Golfo de México para estudiar su posible correlación con la actividad sísmica.La costa del Pacífico Mexicano es una de las zonas sísmicas más activas del mundo, debido a la subducción de las placas de Cocos y Rivera bajo la placa de Norteamérica. Los sismos que ocurren en esta parte de México son de gran magnitud y afectan la meseta central del país donde se encuentra la mayor densidad de población. Mientras que en la costa del Golfo de México, que presenta una actividad sísmica relativamente baja, se tiene localizada la planta nuclear de Laguna Verde (PNLV) por lo que los estudiosde sismicidad deben conocerse por cuestiones de seguridad nuclear.La determinación de la concentración del radón tanto en suelo como en agua subterránea se llevó a cabo con mediciones de largo periodo, utilizando detectores sólidos de trazas nucleares (LR-115). Eventualmente se utilizaron detectores automáticos para mediciones continuas que registran las fluctuaciones de la concentración del radón en tiempos cortos (sonda Clipperton). En algunos casos se analizó la radiación gamma en suelo utilizando detectores termoluminiscentes (CaSO4:Dy+PTFE). La medida de parámetros fisicoquímicos in situy en laboratorio se realizó por métodos físicos y químicos convencionales. Los elementos traza se obtuvieron utilizando un espectrómetro de masas con plasma de acoplamiento inductivo (ICP-MS). El análisis estadístico se llevó a cabo mediante el análisis de componente principal. Se obtuvo la composición mineralógica de muestras de roca, mediante técnicas convencionales y microscopía electrónica de barrido, para determinar la composición química elemental de algunas muestras; para identificar los tipos de compuestos cristalinos se utilizó un difractrómetro de rayos X. La localización de los sitios de muestreo se llevó a cabo mediante un sistema global de posicionamiento (GPS). El muestreo se realizó a lo largo de la costa de Guerrero, desde Guacamayas, Mich. hasta Marquelia, Gro., de 1993 a 1998; en cuanto a la costa del Golfo de México, éste se llevó acabo en la PNLV y sus alrededores de 1994 a 1996.Las fluctuaciones de la concentración de radón, dosis gamma, elementos químicos mayores y trazas, se analizaron en función de los parámetros meteorológicos, las características geológicas y la actividad sísmica local. En la zona de la PNLV, los resultados muestranque por lo general los promedios de los valores de la concentración de radón fueron bajos. Las variaciones de los valores de la concentración de radón tanto en el suelo como en el agua subterránea, fueron diferentes en cada estación de muestreo y están en función de los parámetros meteorológicos y de las características geológicas. La estación de Rancho Nuevo localizada en una zona de falla, al norte de la PNLV fue la que presentó los valores más altos de concentración de radón. Los valores más bajos seobtuvieron en la estación de la PNLV. Las fluctuaciones de la concentración de radón en el suelo fueron mayores que la concentración de radón en agua. Las anomalías de los valores de la concentración del radón se presentaron durante la época de lluvias,este comportamiento quizás se deba a la humedad del suelo ya que coincide con la época de mayor precipitación. Se observó una mayor mineralización en los análisis de los elementos químicos mayores y traza en las muestras de agua subterránea en la época de lluvias. La actividad sísmica durante el periodo de muestreo fue esporádica y de baja intensidad y sólo se pudo observar que la zona de falla fue la que tuvo valores de la concentración de radón mayores, debido a la circulación preferente de gases. En cuanto a la costa del Pacífico, se observó que las fluctuaciones de la concentración del radón en suelo muestran ocasionalmente dependencia con los parámetros meteorológicos. Los valores máximos de la concentración de radón se obtuvieron principalmente enla época de lluvias. El factor primordial que influyó en la concentración del radón fue la geología local de los sitios de estudio, es decir, la respuesta del radón en el suelo depende del tipo de sustrato. Las estaciones de muestreo de radón ubicadas en suelo residual, indicaron valores menores que aquellas que están ubicadas en suelo granítico y metamórfico; así mismo las estaciones cercanas entre sí y que corresponden a la misma región geológica presentan un comportamiento parecido. Se observó una intensa actividad sísmica en el periodo de muestreo. La mayoría de los sismos fueron de magnitud (M>4) y someros (<20 km). La concentración del radón en suelo medido en periodos largos de tiempo no pareció responder con picos uno a uno a los sismos locales, pero muestra las variaciones globales en una zona de alta actividad sísmica, ya que se observaron paquetes de la concentración de radón antes y después de la ocurrencia de algunos sismos. La concentración de los elementos químicos de los sitios muestreados fue diferente, esto se debe a la diversidad del tipo de rocas por donde circula el agua, así como a los mecanismos de recarga. Se observaron incrementos en la concentración de los elementos químicos en la época de secas. Las variaciones de la concentración de radón y de la dosis gamma mostraron en algunos casos una correlación fuerte entre sí, lo cual puede explicarse por el hecho que el dosímetro termoluminiscente se colocó dentro de la cámara de exposición de radón. Las diferencias en composición de los tipos de rocas mostraron diferencias tanto en la emanación de radón como en los niveles de dosis gamma en la zona estudiada. En la correlación por grupos de los elementos químicos mayores y trazas obtenidos en las muestras de agua, se observó una separación geoquímica de los grupos, definiendo así que se trata de acuíferos que provienen de diferentes tipos de formaciones rocosas. La respuesta de las características geoquímicas para cada acuífero estudiado en el presente trabajo depende del contexto geológico específico.